Energy-Efficient Scheduling of Uniform Parallel Machines Problem with Deterioration Effect - Sekkal, Norelhouda; Elouchdi, Mouna; Bakdi, Khadidja (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Uniform Parallel Machine (UPM) scheduling problems have received considerable attention due to their numerous industrial applications. These systems are, however, prone to deterioration. Therefore, preventive maintenance activities are integrated to the system, creating unavailability periods. Meanwhile, deterioration and maintenance activities increase the energy consumption in the workshop. And with growing concerns about the environment and global warming, energy consumption has become a priority for manufacturers. Thus, we treat a uniform parallel machine scheduling problem with deterioration effect and maintenance activities to minimize the total energy consumed. First, we present a mathematical programming model. This model is not able to provide a solution for medium instances in an affordable computational time. However, we adapt to our problem a simulated annealing algorithm. To evaluate the efficiency of the algorithm, we test it and c results with the mal solutions given by the model. Then, we test the algorithm for medium and large instances.